Neutron scattering studies of low-dimensional quantum magnets - Macdougal, D (2019)
This thesis presents studies of the spin dynamics in quantum magnets using inelastic neutron scattering (INS) and linear spin wave theory (LSWT). The first system considered is Ba2CuTeO6, proposed to realise weakly-coupled antiferromagnetic two-leg spin-1/2 ladders. Ba2CuTeO6 orders magnetically, but with a small Neel temperature relative to the exchange strength, suggesting that the interladder couplings are only just able to stabilise magnetic order and placing Ba2CuTeO6 close in parameter space to the critical point separating the singlet phase and Neel order. By comparing powder INS data with LSWT and quantum Monte Carlo (QMC) calculations, values are proposed for all relevant exchange parameters, which place the system on the ordered side of the phase diagram in proximity to the critical point. High-field magnetisation data are also compared with the QMC predictions. In addition, single-crystal INS measurements are presented of the spin-1/2 triangular antiferromagnet Ba3CoSb2O9. Sharp magnons are observed throughout the Brillouin zone with a strong scattering continuum extending up to at least 4x the maximum one-magnon energy. The magnon energies are strongly renormalised downwards and the intensity decreases faster upon increasing energy than predicted by LSWT, which is attributed to a transfer of spectral weight to the continuum. An empirical model of renormalisations to the LSWT dispersion is proposed that can capture quantitatively the magnon dispersions throughout the Brillouin zone. Consistent with the observation of sharp magnons throughout, it is explicitly verified that kinematic constraints disallow one- to two-magnon decays for this renormalised dispersion. There is considerable structure and signal extending to much higher energies that cannot be explained by two-magnon simulations, suggesting significant quantum fluctuations beyond LSWT. The magnon dispersions have also been measured in fields up to 9 T, observing an evolution of the dispersion relations in field that is consistent with the presence of two equal-weight domains of opposite chirality.